Spatial mobility of the population in Santa Catarina: An analysis of urbanization trends through demographic censes - Ambrósio, Marchante Olímpio Assura; Espindula, Edenir Erimar; Wolff, Raquel Holtrup; Coelho, Rodrigo Leopoldo Mendes; Nascimento, Vinicius; Liesenberg, Veraldo (Revista de Ciências Agroveterinárias, 2024)
This study discusses the use of spatial analysis metrics in a Geographic Information Systems (GIS) environment applied to population census data from the Brazilian Institute of Geography and Statistics (IBGE) from the years 2000 and 2010 to understand the complex and multifaceted spatial mobility in Santa Catherine. For this, quantitative data collected in the different administrative regions of the state of SC were used. The phenomenon, observed in several countries, involves population density in metropolitan regions, motivated by the search for better living conditions and catalyzed by the rural exodus due to technological advances in agriculture and the employment of temporary labor. This movement, generally originating in smaller municipalities towards larger ones, has significant consequences for the economic, social and environmental dynamics of the places involved, directly affecting the quality of life of individuals. The municipalities of São Pedro de Alcântara, Ituporanga, Campo Alegre and Bom Retiro, in this 10-year period, showed a considerable rural exodus, with a drop in population of -34.48%, -5.24%, -5.29% and -4.03% respectively, while the increase in the urban population occurred in the regions of Norte Catarinense, Vale do Itajaí and Grande Florianópolis, with emphasis on the following municipalities: Massaranduba, Garopaba, Guabiruba, Tijucas, Florianópolis, Blumenau and Joinville, with 64.31% , 42.88%, 41.65%, 38.97%, 22.01%, 21.84% and 19.97%, respectively. This information is useful for public managers in defining ways to provide resources, infrastructure and services, given the demand for housing, sanitation, education, health, among others.